2012
DOI: 10.1371/journal.pone.0051409
|View full text |Cite
|
Sign up to set email alerts
|

Development of Eye Position Dependency of Slow Phase Velocity during Caloric Stimulation

Abstract: The nystagmus in patients with vestibular disorders often has an eye position dependency, called Alexander’s law, where the slow phase velocity is higher with gaze in the fast phase direction compared with gaze in the slow phase direction. Alexander’s law has been hypothesized to arise either due to adaptive changes in the velocity-to-position neural integrator, or as a consequence of processing of the vestibular-ocular reflex. We tested whether Alexander’s law arises only as a consequence of non-physiologic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
5
3
Order By: Relevance
“…However, the Doslak model also predicts that the velocity-versus-position slope should be independent of nystagmus speed (above a threshold), but that is not the case in our study (Fig. 4c), nor with caloric stimulation (Bockisch et al 2012). The model of Doslak et al also predicts Alexander's law should occur with the normal VOR, yet it is not found with 0.5-Hz sinusoidal head rotations on a turntable (Robinson et al 1984) or head impulses (Anagnostou et al 2011;Anastasopoulos and Anagnostou 2012).…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…However, the Doslak model also predicts that the velocity-versus-position slope should be independent of nystagmus speed (above a threshold), but that is not the case in our study (Fig. 4c), nor with caloric stimulation (Bockisch et al 2012). The model of Doslak et al also predicts Alexander's law should occur with the normal VOR, yet it is not found with 0.5-Hz sinusoidal head rotations on a turntable (Robinson et al 1984) or head impulses (Anagnostou et al 2011;Anastasopoulos and Anagnostou 2012).…”
Section: Discussioncontrasting
confidence: 76%
“…With normal, reciprocal stimulation of the canals, the gain changes with eye position cancel, producing a VOR that does not depend on eye position. Thus, this model does not predict Alexander's law during constant acceleration protocols, as we observed here, nor with bilateral bithermal caloric stimulation (Bockisch et al 2012). Constant acceleration and caloric stimulation protocols that show Alexander's law produce very low-frequency stimulation, whereas the VOR studies that do not show Alexander's law use higher-frequency stimuli.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations